The converging role of traditional leaders and non-traditional leaders in conflict resolution the cases of the sultanate of Marawi, Philippines and Negeri Batu Merah, Ambon City, Indonesia - Panganting, Abdulwahid H.G (Asian Center, University of the Philippines Diliman, 2020)
The traditional communities in Southeast Asia such as the Sultanate of Marawi in Mindanao, Philippines and Negeri Batu Merah in Maluku, Indonesia continue to practice the traditional form of government alongside with the government bureaucracy. In the community level, these two types of institutions--traditional and bureaucracy, enforce laws and render services to the community simultaneously through their respective agents, namely: the traditional leaders and non-traditional leaders while drawing legitimacy from traditional and cultural mores, and the state's constitution, respectively. However, as these two authorities do not have specific functions that delineate one from the other in the community such as in dispoute settlement, their roles often draw confusion as the two often converge, contradict, and complement. This study attempts to compare the role of traditional leaders and non-traditional leaders in land conflict resolutions in the two traditional communities and to explain the convergence of their role in the execution of their respective authority--traditional authority and government authority--relative to land conflict. It particularly focuses on comparing the mechanism used in land conflict resolution, the concept of adat, the indigenous strategies on land conflict resolutions, the colonial legacies, and the contemporary government laws and policies on traditional leaders as these influence the traditional leaders' stature and function today in the traditional community. This is a qualitative study, in particular, a case study as a research method. Key informant and library research (secondary data analysis) are used as data-gathering technique. --Provided by the author